2011
DOI: 10.1038/jes.2011.10
|View full text |Cite
|
Sign up to set email alerts
|

Potential for exposure to engineered nanoparticles from nanotechnology-based consumer spray products

Abstract: The potential for human exposure to engineered nanoparticles due to the use of nanotechnology-based consumer sprays (categorized as such by the Nanotechnology Consumer Products Inventory) is examined along with analogous products, which are not specified as nanotechnology-based (regular products). Photon correlation spectroscopy was used to obtain particle size distributions in the initial liquid products. Transmission electron microscopy was used to determine particle size, shape, and agglomeration of the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
91
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(107 citation statements)
references
References 43 publications
(47 reference statements)
16
91
0
Order By: Relevance
“…While this database might not describe all relevant consumer products due to a very dynamic nature of the market, it does provide an excellent idea about the wide-spread application of nanoparticles in consumer markets. In addition, recent research indicated that nanosized materials might even be present in consumer products not labeled as nanotechnology-based (Nazarenko et al, 2011;Nazarenko et al, 2012b). Among the nanomaterials introduced into the consumer products, Ag, TiO2, ZnO, Pt and SiO2 nanoparticles seem to be the most commonly used (Frohlich and Roblegg, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…While this database might not describe all relevant consumer products due to a very dynamic nature of the market, it does provide an excellent idea about the wide-spread application of nanoparticles in consumer markets. In addition, recent research indicated that nanosized materials might even be present in consumer products not labeled as nanotechnology-based (Nazarenko et al, 2011;Nazarenko et al, 2012b). Among the nanomaterials introduced into the consumer products, Ag, TiO2, ZnO, Pt and SiO2 nanoparticles seem to be the most commonly used (Frohlich and Roblegg, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies found varying contents of NPs in sprays. Advertising the use of nanotechnology did not necessarily mean the presence of NPs, and a number of sprays without reference to nanotechnology contained NPs (Nazarenko et al, 2011, Quadros & Marr, 2011.…”
Section: Introductionmentioning
confidence: 99%
“…These nanotechnology-based consumer sprays are now leading to increased risk of exposure to humans and other organisms (Nazarenko et al 2011). The consequent concerns have resulted in considerable researches on their toxicity (Nel et al 2006;Larese et al 2009;Song et al 2009).…”
Section: Introductionmentioning
confidence: 99%